Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Retensi Pelanggan Beras pada Usaha Penggilingan Padi PB Sinar Laksana Desa Karanganyar Kecamatan Klari Kabupaten Karawang - Aisah Aisah; Aji Tuhagana; Dini Yani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This research was conducted to examine how product quality and consumers’ perceptions of price influence customer loyalty at PB Sinar Laksana’s rice milling enterprise located in Karanganyar Village, Klari District, Karawang Regency. A quantitative research design with a verification approach was applied. The sample consisted of 113 participants drawn from a total population of 385 customers using probability sampling methods. Data collection was carried out online through Google Forms utilizing a Likert scale questionnaire. The collected data were processed using SPSS version 26, including tests of validity, reliability, classical assumptions, multiple linear regression, partial (t-test) and simultaneous (F-test) hypothesis testing, as well as determination coefficient analysis. The findings from the t-test indicated that product quality significantly and positively contributed to customer retention. In contrast, price perception did not show a significant influence, as rice is categorized as a staple good with relatively inelastic demand. The F-test results showed that product quality and price perception simultaneously had a significant effect on rice customer retention at the PB Sinar Laksana rice mill in Karanganyar Village, Klari District, Karawang Regency.